Piloting body-worn cameras in Northern Canada - Khanizadeh, Ariane (Building trust, effective communication, and transparency between police and community members, 2024)
The Royal Canadian Mounted Police (RCMP) are implementing body-worn cameras (BWCs) across the country. This chapter reports on a pilot project designed to evaluate the implementation of these cameras that was conducted in Iqaluit, Nunavut, a remote northern Canadian community. Findings from several surveys – one focusing on community members and the others focusing on RCMP officers – are presented, and the impact on operational data (e.g., crime trends) is discussed. These findings suggest that BWCs are generally supported by the public and although crime and use-of-force rates during the pilot project did not differ from historical trends, BWCs were generally perceived to increase public safety and help improve police-public relations. RCMP officers are also generally satisfied with their BWCs and their BWC training. The authors believe this pilot project helped develop community trust around the use of BWCs by RCMP officers and they hope the project description provides a blueprint for other agencies to implement their own culturally sensitive and community-focused BWC program.